Probability of simultaneous parallax detection for free-floating planet microlensing events near Galactic Centre. Issue 3 (17th April 2020) - Ban, M
ABSTRACT: The event rate and the efficiency of mass estimation for free-floating planet (FFP) microlensing events were determined from the simulation of the simultaneous parallax observations by Euclid, WFIRST, and LSST. The stellar population from the Besançon Galactic model toward ( l, b ) = (1°, −1.°75) was applied to our 3D microlensing model, and 30 000 parallax observations were simulated for each following FFP lens masses: Jupiter mass, Neptune mass, and Earth mass assuming the population of one FFP per star. The interstellar dust, unresolved stellar background, nearby star blending was modelled. A signal-to-noise limit considering a finite source effect determined the event detectability. The Euclid – WFIRST combination yielded 30.7 Jupiter-mass FFPs during two 30-d periods per year in parallax observation. The parallax event rate decreases to 3.9 FFPs for Earth-mass planets. The mass estimation from the parallax light curve allowed recovery of FFP masses to within a factor of 2 for 20–26 per cent of cases. The Euclid –LSST combination yielded 34.5 Jupiter-mass FFPs down to 0.5 Earth-mass FFPs for the same periods and the mass is recovered to within a factor of 2 in 20–40 per cent of cases. The event rate will be normalized by the unknown FFP abundance to recover the number of expected detections.